Anabolic androgenic steroids and cardiomyopathy: an update - Fadah, Kahtan; Gopi, Gokul; Lingireddy, Ajay; Blumer, Vanessa; Dewald, Tracy; Mentz, Robert J. (Frontiers in Cardiovascular Medicine, 2023)
Anabolic androgenic steroids (AAS) include endogenously produced androgens like testosterone and their synthetic derivatives. Their influence on multiple metabolic pathways across organ systems results in an extensive side effect profile. From creating an atherogenic and prothrombotic milieu to direct myocardial injury, the effects of AAS on the heart may culminate with patients requiring thorough cardiac evaluation and multi-disciplinary medical management related to cardiomyopathy and heart failure (HF). Supraphysiological doses of AAS have been shown to induce cardiomyopathy via biventricular dysfunction. Advancement in imaging including cardiac magnetic resonance imaging (MRI) and additional diagnostic testing have facilitated the identification of AAS-induced left ventricular dysfunction, but data regarding the impact on right ventricular function remains limited. Emerging studies showed conflicting data regarding the reversibility of AAS-induced cardiomyopathy. There is an unmet need for a systematic long-term outcomes study to empirically evaluate the clinical course of cardiomyopathy and to assess potential targeted therapy as appropriate. In this review, we provide an overview of the epidemiology, pathophysiology and management considerations related to AAS and cardiomyopathy.